Faktor-faktor yang Berpengaruh pada Kesetiaan Nasabah Lembaga Kredit Mikro Bank Perkreditan Rakyat, Koperasi Simpan Pinjam dan Yayasan di Kabupaten Malang - Khusnul Ashar (Jurnal Aplikasi Manajemen, 2011)
An objective of this research is to identify effect of reliability factor, responsiveness, and empathy from credit service and officer either on loyalty or discipline of customer. In addition, it identifies effect of loyalty on discipline of customer. Sampling method used is purposive incidental sampling to obtain 330 respondents of customer of MCI in form of People Credit Bank (Bank Perkreditan Rakyat/BPR), Cooperative of Saving and Loan (Koperasi Simpan Pinjam/KSP) and Foundation in region of Karang Ploso Sub District, Malang RegencyThe dependent variable is customer loyalty and discipline. Result of hypothesis test indicated that factors significantly influencing on customer loyalty is credit reliability, credit empathy and officer reliability. Statistically, the most influencing factor is credit reliability followed by factor of credit empathy and the least influencing factor is officer reliability. There seems no real effect of loyalty on customer discipline.Keywords: Customer loyalty, Credit micro institution